Study of Coal Combustion Waste Utilization: Coal Fly Ash for Adsorption of Pb(II), Cd(II), BOD and COD in Donan River Water Samples: Studi Pemanfaatan Limbah Pembakaran Batubara: Abu terbang Batubara untuk Adsorpsi Pb(II), Cd(II), BOD dan COD pada Sampel Air Sungai Donan - Rohmah, Dini; Khuzaimah, Siti; Alimah, Gustin Nur (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2024)
The Donan River is the largest source of fresh water in Cilacap Regency. The existence of industrial areas and densely populated residential areas in river basins makes river water polluted. On the other hand, the Karangkandri PLTU industry in Cilacap has coal burning waste in the form of fly ash which can be used for heavy metal adsorption and water pollutant adsorption. The aim of this research is to determine the effectiveness of fly ash for the adsorption of metal ions Pb(II), Cd(II), BOD and COD in Donan River water. Water from the Donan River were taken at 3 points, from the three sampling points it was proven that the water quality of the River was above the class III water threshold. The next step was to tested the fly ash adsorbent which has been activated with H2SO4. The effectiveness test of the fly ash adsorbent included testing the ability to absorb Pb(II) and Cd(II) metal ions and reduce BOD and COD levels in 500ml sample water with an adsorbent mass of 100g, three of water sample as independent variable. Research showed that fly ash adsorbents were able to reduce water pollutant levels with a maximum capacity of 80%.